Optimalisasi UMKM Berbasis Syariah: Studi Kasus Browsist Dalam Pengembangan Ekonomi Kreatif Kuliner - Friska Efia Akwila; Filzah Aulia (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2025)
Small and medium enterprises (SMEs) play a very important role in the economy, especially in developing countries like Indonesia. Developing countries such as Indonesia. This research aims to develop mentoring strategy for SMEs in the snack food sector, specifically “BROWSIST,” which faces challenges in digital marketing,operational efficiency, and implementation of sharia economic principles. Through qualitative descriptive approach, this research conducts mentoring with a focus on optimizing digital marketing, improving operational management, and integrating sharia principles in every aspect of the business. integration of sharia principles in every aspect of the business. The results of the mentoring showed a significant increase in turnover, number of customers, and operational efficiency after three months. efficiency after three months. In addition, stronger application of sharia principles in business transactions and finances principles in business transactions and finances strengthens BROWSIST's position in the halal market. halal market. This study suggests the importance of sustainability in brand development, increasing production capacity, and expanding market reach to support more sustainable business growth. market to support more sustainable business growth.